2019
DOI: 10.1177/1368430219849690
|View full text |Cite
|
Sign up to set email alerts
|

On the way to fusion through the pilgrims’ route: Factors that maintain identity fusion in collective rituals

Abstract: Identity fusion, a visceral union between personal and group identity is considered to be triggered and maintained by collective rituals with certain characteristics (e.g., opaque causal actions, synchrony, high excitement) and by recalling such rituals. The purpose of the present research was to determine the factors that maintain identity fusion after taking part in the pilgrimage of the Way of Saint James. We conducted a study with pilgrims ( N = 609) to analyze the factors associated with the characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Our studies are not alone in reaching this conclusion. Lobato and Sainz (2019) observed participants' identity fusion after a pilgrimage, thus further confirming that costly rituals entail social cohesion. Long-term effects of social cohesion were not predicted by intrapersonal variables (material remembrances; symbolic memories; reminiscent thoughts) but well by contacts with other pilgrims.…”
Section: Discussionsupporting
confidence: 56%
“…Our studies are not alone in reaching this conclusion. Lobato and Sainz (2019) observed participants' identity fusion after a pilgrimage, thus further confirming that costly rituals entail social cohesion. Long-term effects of social cohesion were not predicted by intrapersonal variables (material remembrances; symbolic memories; reminiscent thoughts) but well by contacts with other pilgrims.…”
Section: Discussionsupporting
confidence: 56%
“…Other studies also found support for the idea that participating in collective gatherings, like folkloric marches and religious celebrations, could increase fusion (e.g., Páez, Rimé, Basabe, Wlodarcsyk, & Zumeta, 2015; Zumeta, Basabe, Wlodarczyk, Bobowik, & Páez, 2016). Finally, recent investigations show that engaging in ritual practices and recalling episodic memories of pilgrim's route contribute to maintain identity fusion (Lobato & Sainz, 2019).…”
Section: Main Advances and Discoveries Since 2015 For Identity Fusionmentioning
confidence: 99%
“…In collective rituals, the social identity is enhanced leading to a high sense of belonging to the ingroup (Drury & Reicher, 2009;Khan et al, 2016) and to a fusion of one's personal identity with the ingroup identity (Lobato & Sainz, 2019). Fusion of identity goes beyond group identification, strengthening the social cohesion between members (Buhrmester et al, 2012).…”
Section: Collective Gatherings and Ritualsmentioning
confidence: 99%